1999
DOI: 10.1007/s004420050748
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in biomass and nutrient allocation of first-year Silene dioica plants

Abstract: Reproductive and somatic biomass, nitrogen (N), and phosphorus (P) pools were compared between females and males in 1st-year plants of Silene dioica. We estimated irretrievable resources allocated to seeds, pollen, flowers, and unrecovered summer leaf investment by collecting plant parts at abscission throughout the season. At the end of the season, we determined resources lost through senescent stems and autumn leaf turnover and resources stored in perennial roots and overwintering buds. Sexual differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…As reproductive costs could be demonstrated in 75% of more than 80 examined studies (Obeso 2002), our results are contradictory to the majority of these studies. Our results do, however, concur with previous findings that reproductive costs may be difficult to detect in long-lived plants in harsh environments (Hemborg and Karlsson 1999) and that high reproductive effort in one year sometimes has little effect on next year's reproductive output (Horvitz andSchemske 1988, Jennersten 1991). Such lack of reproductive cost can be explained in several ways.…”
Section: Discussionsupporting
confidence: 91%
“…As reproductive costs could be demonstrated in 75% of more than 80 examined studies (Obeso 2002), our results are contradictory to the majority of these studies. Our results do, however, concur with previous findings that reproductive costs may be difficult to detect in long-lived plants in harsh environments (Hemborg and Karlsson 1999) and that high reproductive effort in one year sometimes has little effect on next year's reproductive output (Horvitz andSchemske 1988, Jennersten 1991). Such lack of reproductive cost can be explained in several ways.…”
Section: Discussionsupporting
confidence: 91%
“…Harris & Pannell, 2008;but see Å gren, 1988), which is more strongly limited by C stores (Ishida et al, 2005). Hemborg & Karlsson (1999) also found that females of Silene dioica have greater allocation of N to overwintering organs than males. For S. latifolia, corm resources are remobilized at the beginning of the growing season and corms wither completely by the time the plant is established in early summer.…”
Section: Investment In Male Vs Female Functionmentioning
confidence: 86%
“…In this system, repeated weather changes are therefore essential in driving beetles from male to female plants, exporting pollen in the process. Contradicting the advantage of large floral displays is the fact that they can be costly to produce (Hemborg & Karlsson, 1999) and involve high risks of dying prematurely, i.e. before the next fire (Bond & Maze, 1999).…”
Section: Discussionmentioning
confidence: 99%